Performance Characteristics of Cemented Tailings Containing Crumb Rubber as a Filling Material - Zhuoqun Yu; Nan Qin; Sa Huang; Jianguang Li; Yongyan Wang (Advances in Materials Science and Engineering)
Increasing amounts of tailings and waste rubber tires have caused threats to the environment. In order to reuse these solid wastes, this study proposed a cemented tailings material containing crumb rubber recovered from waste tires. Unconfined compression tests and thermal conductivity measurements were conducted to evaluate the feasibility and performance of the proposed cemented tailings. Results revealed that the stress-strain behavior of the cemented tailings changed by the inclusion of crumb rubber. The unconfined compressive strength of cemented tailings decreased with increasing crumb rubber content. The inclusion of crumb rubber increased the failure strain and nonlinearity index of the cemented tailings. It was found that the addition of 4% crumb rubber provided the greatest improvement in ductility. The increase of the rubber content further increased the thermal insulation capacity of the cemented tailings. The low stiffness and the dimpled surface of the crumb rubber were responsible for the reduced compressive strength and thermal conductivity of the cemented tailings. In conclusion, the crumb rubber had both positive and negative effects on the cemented tailings. In practical application, the rubber admixture amount should be flexibly adjusted for different use case to make the cemented tailings material show the most suitable performance characteristic.